Wild-Type Mitochondrial DNA Copy Number in Urinary Cells as a Useful Marker for Diagnosing Severity of the Mitochondrial Diseases - Liu, Hui; Ma, Yinan; Fang, Fang; Zhang, Ying; Zou, Liping; Yang, Yanling; Zhu, Sainan; Wang, Songtao; Zheng, Xuefei; Pei, Pei; Li, Lin; Wu, Hairong; et al. (PLOS ONE, 2013)
The genotype-phenotype relationship in diseases with mtDNA point mutations is still elusive. The maintenance of wild-type mtDNA copy number is essential to the normal mitochondrial oxidative function. This study examined the relationship between mtDNA copy number in blood and urine and disease severity of the patients harboring A3243G mutation. We recruited 115 A3243G patients, in which 28 were asymptomatic, 42 were oligo-symptomatic, and 45 were poly-symptomatic. Increase of total mtDNA copy number without correlation to the proportion of mutant mtDNA was found in the A3243G patients. Correlation analyses revealed that wild-type mtDNA copy number in urine was the most important factor correlated to disease severity, followed by proportion of mutant mtDNA in urine and proportion of mutant mtDNA in blood. Wild-type copy number in urine negatively correlated to the frequencies of several major symptoms including seizures, myopathy, learning disability, headache and stroke, but positively correlated to the frequencies of hearing loss and diabetes. Besides proportion of mutant mtDNA in urine, wild-type copy number in urine is also an important marker for disease severity of A3243G patients.